A Review of Current Data on Duration of Effect in Glabellar Lines After Treatment With AbobotulinumtoxinA 50 U - Cohen, Joel L; Cox, Sue Ellen; Glaser, Dee Anna; Moradi, Amir; Dayan, Steven; Jacob, Carolyn; Schlessinger, Joel; Joseph, John; Kaufman-Janette, Joely; El-Qadi, Sami; Persson, Cecilia; Prygova, Inna (Dermatologic surgery, 2024)
AbobotulinumtoxinA has become well established as a treatment option for moderate to severe glabellar lines since its first aesthetic approval in 2009. Pivotal trials leading to regulatory approval showed that abobotulinumtoxinA treatment was associated with high responder rates when defined as achievement of none or mild glabellar lines (0 or 1 on the glabellar line severity scale) and a duration of action of up to 5 months. More recently, the goals for treatment of glabellar lines have shifted toward not only achieving a decrease in glabellar line severity but also ensuring that patients are satisfied with their experience. Patients seek an improvement in the appearance of their glabellar lines while maintaining a "natural look," fast onset of effect, and long duration of response. Trial designs have evolved to meet these new targets, including expanding the definition of responders to those having at least 1-grade improvement in the glabellar line severity scale score from baseline coupled with the use of subject satisfaction and psychological well-being questionnaires. The findings demonstrate that abobotulinumtoxinA remains a well-tolerated and consistently effective treatment option associated with a rapid onset of effect, duration of efficacy lasting up to 6 months, and high, long-lasting levels of patient satisfaction.